Management of The Wampu River in Reducing Flood Risk in Tanjung Pura District, Langkat Regency - Supardi Sitepu; Abdi Sugiarto; Cut Nuraini (Equivalent : Journal of Economic, Accounting and Management, 2026)
Recurrent flooding in Tanjung Pura District, Langkat Regency, has had a significant impact on the community and infrastructure. This study aims to analyze the physical condition of the Wampu River, the factors causing the flooding, its impact on the community and infrastructure, and sustainable river management strategies. This study used a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldana (2014). The Results indicate that river channel siltation, land use changes, high rainfall, and infrastructure damage are the main causes of flooding. These recurring floods impact homes, agricultural land, public facilities, and public health and well-being. Effective river management strategies include watershed rehabilitation, flood control infrastructure improvements, sedimentation control, increased community participation, and inter-agency coordination. This study provides recommendations for policymakers and the community to implement sustainable river management in flood risk mitigation efforts.